STUDI PEMIKIRAN IMAM SYAFI'I TENTANG DISIPLIN ILMU DAN RELEVANSINYA BAGI MANAJEMEN PEMBELAJARAN PENDIDIKAN ISLAM - Sapri; Anggi Khairani; Kenara; Anugrah Akbar; Fira Dwi Putri; M. Ali Akbar; Alfie Ridho (STKIP Subang, 2025)
Ideally, Islamic education should not only focus on the transfer of religious knowledge, but also on the formation of systematic, disciplined, and responsible thinking patterns in the management of knowledge. However, the reality of contemporary Islamic education shows a weak epistemological framework of learning, overlapping material, and low methodological consistency, which results in ineffective learning management. In this context, Imam Syafi'i's thinking is considered relevant to be re-examined as the epistemological and managerial foundation of Islamic education. This study aims to describe the concept of scientific discipline according to Imam Syafi'i and analyze its relevance to contemporary Islamic education learning management. This study uses a qualitative approach with library research, sourced from Imam Syafi'i's primary works, particularly al-Risālah and al-Umm, as well as relevant secondary literature. Data analysis was conducted through content analysis with a descriptive-interpretative and historical-philosophical approach. The results of the study show that the discipline of Imam Syafi'i's thinking is built on three main principles, namely tartib al-adab, intizam al-wad', and istiqamah al-manhaj, which integrally form an epistemological and managerial framework for learning. These three principles are strongly relevant to the functions of Islamic education learning management, which include planning, organizing, implementing, and evaluating (POAC). This study confirms that Imam Syafi'i's thinking is not only of historical-normative value but also has practical significance in developing a systematic, disciplined, and character-building approach to Islamic education management that focuses on the holistic development of students' scientific character.